Figurative Language Used in Children’s Songs in the 1990s and 2000s - Wisran Wisran (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aims to: (1) To find out the types of figurative languages used in children's songs in the 1990s and 2000s (2) To analyze the contextual meanings of figurative language used in children's songs in the 1990s and 2000s. The data in this study are in the form of words. Data obtained by using the method of observation and documentation method. The data analysis used is descriptive qualitative. Data is presented in formal and informal forms. The results of data analysis in this study found the types of figurative language in children's songs in the 1990s, namely simile, metaphor, personification, symbolic, paradox and hyperbole. While in children's songs in the 2000s, the types of figurative language used are simile, metaphor, personification, metonymy, symbolic, paradox, hyperbole and